The Sandwich Dual-Tissue Salvage: Synergistic Anteriorly-Based Tongue Flap and Autologous Dermofat Graft for Recalcitrant Pittsburgh Class V-VI Palatal Fistulas - Anak Agung Gde Rama Kaesara; Putu Trisna Utami (HM Publisher, 2026)
Background: Recurrent palatal fistulas following cleft palate repair, particularly Pittsburgh Class V and VI defects, represent a distinct reconstructive challenge characterized by tissue ischemia, scarring, and volumetric deficiency. The